Using participatory design and visual narrative inquiry to investigate researchers' data challenges and recommendations for library research data services. Issue 4 (1st September 2015) - Andrew Cox, Dr; Mattern, Eleanor; Jeng, Wei; He, Daqing; Lyon, Liz; Brenner, Aaron
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to report on an information gathering study on users' research data-related challenges and proposals for library research data services (RDS). This study probes how early career researchers visually conceptualize the research process in their disciplines, their self-reported research data challenges, and their recommendations for library RDS. Design/methodology/approach – Two focus group sessions were undertaken with a total of eight early career researchers. Adopting the visual narrative inquiry method, the participants were asked to sketch the general research process in their domain. The individuals' illustrations of the research process were then used as the basis for reflecting on their data-related needs and potential RDS that would assist them during the research process. Findings – Participants presented a research process that was more personal and, in most cases, more imperfect than the research lifecycle models that academic libraries are increasingly using for RDS development and communication. The authors present their data-related challenges, which included data access barriers, low knowledge of best practices for research data management, the need for a deeper understanding of post-publication impact, and inconsistent awareness of existing library and institution RDS. The authors outline RDS recommendations that participants proposed, which included a web-based tools, customized training sessions, and "distilled" guides to research data best practices. Practical implications – The study flagged users' gaps in understandings of existing library and institutional RDS, suggesting that there may be an opportunity to engage users in the design of communications plans for services. The findings from this user study will inform the development of RDS at the institution. Originality/value – This paper puts forth a methodological approach that academic libraries can adapt for understanding users' needs and user-generated design solutions.